Hepatitis B Virus and Liver Disease (Springer Singapore, 2018)
This book provides a comprehensive, state-of-the art review of HBV infection and liver disease. It discusses new data on basic and translational medicine, including the viral life cycle, the immunopathogenesis of virus-induced chronic hepatitis, viral and host genetic factors affecting disease progression, and the mechanism of virus-induced hepatocarcinogenesis, as well as their potential applications in daily clinical practice. The clinical aspects of chronic HBV infection are examined in chapters on the global epidemiology, efficacy of HBV vaccination, natural history, co-infections with HCV, HDV or HIV, and management of special populations including children, pregnant women and patients undergoing immunosuppressive therapy. Further, it describes the advances and perspectives in the development of novel antiviral treatments as possible cures for HBV infection. The book is a valuable resource for medical students, physicians, and researchers who are interested in management of patients with chronic HBV infection and investigation HBV infection.